The structure and evolution of the HLA--Bw4 and Bw6 antigens. - Barnstable, C; Snary, D; Crumpton, M; Bodmer, W (1979)
The HLA--Bw4 and Bw6 antigenic determinants have been shown to co-migrate with HLA--B determinants on gel-filtration, sucrose density gradient centrifugation and affinity chromatography, using Lens culinaris lectin and antibody against human beta 2 microbulin. These and other published data imply that the HLA--Bw4 and Bw6 determinants reside on the same polypeptide chain as other HLA--B locus determinants. The implications of this in terms of the evolution of cross reacting groups of antigens at the HLA--B locus are discussed.